Why Carl Schmitt (and others) got Kant wrong - Romero, Paola (Con-Textos Kantianos. International Journal of Philosophy, 2021)
This essay traces the influence of Carl Schmitt on an interpretative tendency found in a number of contemporary readings of Kant’s political philosophy. This influence can be traced back to two basic commitments: the idea that Kant’s philosophy (i) seeks to defend a pacifist and humanitarian ideal of history and progress, and (ii) that political conflict must, for this reason, be somehow pacified or eradicated. I argue that these ‘anti-conflict’ readings of Kant go astray in ignoring the systemic role conflict plays in Kant’s understanding of agency and freedom on the one hand, and in overlooking that this conflict is not empirical but normative, and thereby, unavoidable. In light of this ‘agential conflict’, Schmitt’s critique to Kant begins to lose all its force.